Improving the performance of HDPE plastic membranes for heavy metal removal by incorporating EVA/PDMS - Utari Zulfiani; Agus Wedi Pratama; Romario Abdullah; Dinia Astira; Taufik Qodar Romadiansyah; Alvin Rahmad Widyanto; Saiful; Juhana Jafaar; Triyanda Gunawan; Nurul Widiastuti (Results in Engineering)
Plastic waste poses a significant environmental threat. To address this issue and mitigate water pollution caused by heavy metals, this study repurposed HDPE plastic waste into functional membranes. To enhance the membrane's properties, HDPE was blended with EVA to improve hydrophilicity and flexibility, and then coated with PDMS to reduce pore size. These membranes were fabricated using a sustainable and cost-effective TIPS process with mineral oil as a solvent. Characterization techniques, including SEM, FTIR, EDX, contact angle measurement, AFM, and stress-strain analysis, were employed to investigate the morphological, chemical, and mechanical properties of the membranes. Zeta potential measurements were also conducted to assess the surface charge. The performance evaluation revealed that PDMS coating significantly increased the rejection of Ni(II) and Pb(II) ions (up to 63 % and 78 %, respectively), while EVA addition improved the pure water flux (from 16 to 44 L/(m2·h)). The membranes exhibited good performance over a range of pH, contact time, and metal ion concentrations. Additionally, the membranes demonstrated excellent cleaning efficiency with NaOCl and citric acid, maintaining high flux recovery and metal removal rates after multiple cycles. The study's findings highlight the potential of repurposing plastic waste into functional membranes for water treatment applications, contributing to a more sustainable and circular economy.